“Eu continuo (sobre)vivendo, mas é isso?”: análise psicossocial da formação de um coletivo transfeminista da cidade de Blumenau-SC. - Berezoschi, Juliana (2019)
The research accompanies a transfeminist collective from the city of Blumenau / SC - Damas D`Paus - with the objective of analyzing its formation and development in the interface with the life history of its members and with the territory. The method adopted was the action-participant research, therefore, it was developed with the members of the collective: Ághata, Rihanna and Ashley, who, along with the researcher, interfered in the process, aiming at strengthening the collective. All the steps of the research were recorded in a field diary, complemented by testimonies and interviews of the three members of the collective. The theoretical-methodological assumptions are those of socio-historical psychology, based on the reflections of Vygotsky, Silvia Lane and Sawaia on affections, subjectivity and the proposal of the dialectic of social exclusion / inclusion and the ethical-political suffering developed by Sawaia. The presentation of the research was divided into two parts: Itineraries of the Damas D'Paus Transfeminist Collective, which presents the activities of the members in the territory, their interlocutors, advances and obstacles, with emphasis on both the collective and its members. And the other part seeks to analyze the ethical-political suffering that marks the trans and transvestite experiences of the collective in question. One of the highlights of the itinerary was the creation of the Citizenship T project, aimed at developing social inclusion actions carried out by the members themselves, and the candidacy to the state deputy of one of the members in the last election. The methodology of action-participant research appeared as an alternative to practice in social psychology with collectives of transsexuals and transvestites to break with the essentialization of female and male bodies and their role of subalternity to extemporaneous knowledge. In the present case, it has collaborated both to strengthen the collective and the power of each of its participants in the struggle against inappropriate ideas and actions that are perpetrated socially, demonstrating that one does not occur without the other. As a result one can point to the importance of the collective (the feeling and the materiality of the common that constitutes it) and the role of the university in strengthening the emancipation from the destiny that society reserves for them: prostitution, and breaking with aesthetic standards imposed, based on heteronormativity, using social performance as a strategy in search of life potential. However, it should be emphasized that the research also showed that the factor of social and economic inequality crosses cis passability to conquer a job